Edukasi Cara Mengkonsumsi Obat Selama Bulan Ramadhan Di Puskesmas Perumnas Antang Kota Makassar - Besse Yuliana; Imran Firman; Elvira Santi; Safaruddin Safaruddin; Ummu Kalsum; Rizky Indah Pratiwi (Jurnal Pengabdian Masyarakat Farmasi : Pharmacare Society, 2023)
The pattern of drug consumption in the community is very important to be given education considering the many factors that cause the pharmacological ineffectiveness of the desired drug, especially during the holy month of Ramadan. Public knowledge about drugs is still lacking, while drugs must be used properly and correctly so as to provide optimal pharmacological effects. Activities carried out by providing education on how to take medicine during the month of Ramadan at the Perimnas Antang Health Center, Manggala sub-district, Makassar city. The use of drugs during the month of Ramadan must be supported by public knowledge about how to consume drugs that are good and safe. Provision of correct information on the use of drugs is very important for the community to avoid negative impacts on personal health and the environment. The method used in achieving this goal is socialization activities regarding the meaning of drugs, functions, classification of drugs, socialization of various types of drug preparations and methods of consumption and dosage during the holy month of Ramadan to residents of the Manggala sub-district, Makassar City. In outreach activities on how to take drugs properly and correctly during the month of Ramadan, the socialized material will be discussed, namely an explanation of the general definition of drugs, drug classifications consisting of over-the-counter drugs, limited over-the-counter drugs and types of drugs commonly consumed by the general public, especially residents of Antang, Manggala sub-district. Makassar city.